Electrogenerated Chemiluminescence of Semiconductor Nanoparticles and Their Applications in Biosensors. Issue 7 (8th June 2017) - Benoit, Lora; Choi, Jai‐Pil
Abstract: Compared to fluorescence, electrogenerated chemiluminescence (ECL) can be a superior analytical tool in terms of sensitivity and signal‐to‐noise ratios, owing to the absence of background emissions from unwanted photoexcitation. Semiconductor nanoparticles (NPs) are highly promising in many analytical applications, because they can produce stable ECL and possess surface‐dependent, tunable ECL properties. This Minireview gives a brief overview of ECL energetics and processes, the current progress of ECL of semiconductor NPs, and recent advances in biological sensing based on ECL of semiconductor NPs. The current challenges and perspectives on ECL of semiconductor NPs and their biological sensing applications are also discussed. Abstract : Making progress : The energetics and processes of electrochemiluminescence (ECL) are briefly addressed and the current progress of semiconductor nanoparticles in ECL is highlighted. This Minireview also presents relevant biological sensing applications.